The structure and function of FUN14 domain-containing protein 1 and its contribution to cardioprotection by mediating mitophagy - Lv, Yuhu; Yu, Zhengze; Zhang, Peiwen; Zhang, Xiqian; Li, Huarui; Liang, Ting; Guo, Yanju; Cheng, Lin; Peng, Fenglin (Frontiers in Pharmacology, 2024)
Cardiovascular disease (CVD) is a serious public health risk, and prevention and treatment efforts are urgently needed. Effective preventive and therapeutic programs for cardiovascular disease are still lacking, as the causes of CVD are varied and may be the result of a multifactorial combination.Mitophagy is a form of cell-selective autophagy, and there is increasing evidence that mitophagy is involved in cardioprotective processes. Recently, many studies have shown that FUN14 domaincontaining protein 1 (FUNDC1) levels and phosphorylation status are highly associated with many diseases, including heart disease. Here, we review the structure and functions of FUNDC1 and the path-ways of its mediated mitophagy, and show that mitophagy can be effectively activated by dephosphorylation of Ser13 and Tyr18 sites, phosphorylation of Ser17 site and ubiquitination of Lys119 site in FUNDC1. By effectively activating or inhibiting excessive mitophagy, the quality of mitochondria can be effectively controlled. The main reason is that, on the one hand, improper clearance of mitochondria and accumulation of damaged mitochondria are avoided, and on the other hand, excessive mitophagy causing apoptosis is avoided, both serving to protect the heart. In addition, we explore the possible mechanisms by which FUNDC1-mediated mitophagy is involved in exercise preconditioning (EP) for cardioprotection. Finally, we also point out unresolved issues in FUNDC1 and its mediated mitophagy and give directions where further research may be needed.